Improving Quality of Wedding Event Management to Reduce Common Mistakes at Mahar Agung Organizer Using the Six Sigma Method - Sakti, Angela Tiara; Kustini, Kustini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to improve the quality of wedding event management at Mahar Agung Organizer using Six Sigma and DMAIC. The data used in this research is data on the number of events managed by Mahar Agung from 2021 to 2023. At the define stage, it was found that the type of defect that most often occurred at wedding events was events that did not run according to the rundown. At the measure stage, the DPMO value was obtained at 103,552 with a sigma value of 2.762. From the results of the analysis using a cause-and-effect diagram, it was found that several main factors caused defects in wedding event operations, including additional events outside the runway, delays in the arrival of vendors or guests, poor communication and crowded guests. In the improve stage, improvements were made to the process to obtain a DPMO value of 23,809 and a sigma value of 3.481, where there was an increase in the sigma value of 0.719. Improvements in service quality are carried out by providing training to official crew, details in event guidebooks, as well as improving communication methods so that the number of errors or defects can continue to decrease